2015
DOI: 10.1007/s10409-015-0405-x
|View full text |Cite|
|
Sign up to set email alerts
|

Hierarchical structure observation and nanoindentation size effect characterization for a limnetic shell

Abstract: In the present research, hierarchical structure observation and mechanical property characterization for a type of biomaterial are carried out. The investigated biomaterial is Hyriopsis cumingii, a typical limnetic shell, which consists of two different structural layers, a prismatic "pillar" structure and a nacreous "brick and mortar" structure. The prismatic layer looks like a "pillar forest" with variationsection pillars sized on the order of several tens of microns. The nacreous material looks like a "bric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 43 publications
(70 reference statements)
2
10
0
Order By: Relevance
“…where H 0 is the reference hardness value corresponding to deep indentation hardness, l is material length scale, h is indent depth, N is strain hardening exponent of material, β describes the angle of the circular conic indenter through area equivalency with true pyramid indenter. The trans-scale mechanics theory considering strain gradient and surface/interface effects was investigated by Song et al [30], the nanoindentation hardness H with respect to indent depth h for the case of circular conic indenter and TBCs can be expressed as…”
Section: Modeling Of Nanoindentation Size Effect For Micron-/nano-gramentioning
confidence: 99%
See 2 more Smart Citations
“…where H 0 is the reference hardness value corresponding to deep indentation hardness, l is material length scale, h is indent depth, N is strain hardening exponent of material, β describes the angle of the circular conic indenter through area equivalency with true pyramid indenter. The trans-scale mechanics theory considering strain gradient and surface/interface effects was investigated by Song et al [30], the nanoindentation hardness H with respect to indent depth h for the case of circular conic indenter and TBCs can be expressed as…”
Section: Modeling Of Nanoindentation Size Effect For Micron-/nano-gramentioning
confidence: 99%
“…The above two types of mechanical properties obtained by the above two scale tests are extremely different. Many studies have shown that an apparent indentation size effect (ISE) of hardness for different kinds of materials was observed, such as brittle materials [26,27], metal materials [28,29], and biomaterials [30]. In order to describe the ISE, a series of different theoretical methods were presented.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The characteristic length of the strain gradient organic matrix is an essential parameter in the proposed model. For metal, this characteristic length is in the order of micron, however for organic material (nacre), its value is also in the order of micron through comparing simulation results with experimental results for nanoindentation test (Song et al, 2015). So, in the following calculations, we will use the values of characteristic length for the organic matrix.…”
Section: Comparisons With Experiments and Simulationmentioning
confidence: 99%
“…interlaminations, the rest 11.9% was in the mineral platelets, which divided the mineral platelet to many aragonite nanograins (Zhang et al, 2016 hardness showed a strong size effect. By a trans-scale mechanics theory (Song et al, 2014;Wu et al, 2012), which considered both strain gradient effect and the surface/interface effect, Song et al (2015) As mentioned above, the organic materials and the immersed mineral bridges, nanoasperities, etc. in the organic interlaminations can be regarded as an effective medium and its properties are size-dependence.…”
Section: Comparisons With Experiments and Simulationmentioning
confidence: 99%